Posted by **Hannah** on Monday, March 19, 2012 at 8:54pm.

Factor

12^2-3

- Algebra 2 -
**Feliz**, Monday, March 19, 2012 at 10:03pm
Factor

12^2 - 3

Factor out 3.

3(4^2 - 1)

- Algebra 2 -
**Steve**, Tuesday, March 20, 2012 at 10:36am
Be sure to check your work:

12^2-3 = 144-3 = 141

3(4^2-1) = 3(16-1) = 3(15) = 45

what happened?

12^2-3 = (3*4)^2-3 = 3*4*3*4 - 3

You can see that the 3 can't just be factored from 12^2, because that would factor out 3^2.

So, what you get is

3(4*3*4-1) = 3(48-1)

## Answer This Question

## Related Questions

- Algebra - Factor at the greatest common factor from the expression. Can someone ...
- Algebra - Factor out the greatest common factor simply the factor if possible. ...
- algebra 2 - f(x) =x^4 - x^3 -4x^2 +4. find factor and graph. I only factor to ...
- Algebra - Use the Factor Theorem to determine whether x+2 is a factor of P(x)=2x...
- algebra--1 question - Suppose you divide a polynomial by a binomial. How do you ...
- Algebra - I'm trying to solve x^3-3x^2-x+3 is less than zero. Except, I'm not ...
- Algebra - Factor out 8x^3y^6 + 27 One factor is 2xy^2+3. (The sum of the cube ...
- science help - Two factors which cause global climate change are listed below. ...
- Algebra 2 - If P(x) is a polynomial in x for which P(3)=0, then..? a) x-3 is a ...
- algebra - How do you factor the difference of two squares? How do you factor the...

More Related Questions